2016
DOI: 10.4238/gmr.15038780
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of genetic diversity and population structure of Houttuynia cordata Thunb with regard to environment

Abstract: ABSTRACT.To study the levels of genetic diversity, and population structure, of Houttuynia cordata Thunb, the genetic background and relationships of populations were analyzed in terms of environmental factors. The genetic diversity and population structure of H. cordata were investigated using sequence-related amplified polymorphisms and correlation with environmental factors was analyzed using the SPSS software. Two thousand one hundred sixty-three sites were amplified from 41 pairs of primers, 1825 of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This could be one reason for observed high genetic variation between regions and low genetic variation among population within region. Similar explanation was also suggested by Zhong et al 2016, where they investigated genetic diversity and population structure of H. cordata Thunb. from China using sequence-related amplified polymorphism (SRAP) marker.…”
Section: Population Structure and Gene Flowsupporting
confidence: 78%
See 1 more Smart Citation
“…This could be one reason for observed high genetic variation between regions and low genetic variation among population within region. Similar explanation was also suggested by Zhong et al 2016, where they investigated genetic diversity and population structure of H. cordata Thunb. from China using sequence-related amplified polymorphism (SRAP) marker.…”
Section: Population Structure and Gene Flowsupporting
confidence: 78%
“…Many studies from China have reported genetic diversity of H. cordata Thunb. based on morphological features, isozyme, chromosome number and ISSR markers (Wu et al 2002(Wu et al , 2003Wei and Wu 2012;Zhong et al 2016). But until now, no study has targeted the genetic diversity and population structure of this important medicinal plant in North-East India, although this information is essential for the formulation of any effective conservation strategies.…”
Section: Introductionmentioning
confidence: 99%